This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
all μ , τ , λ are multiplicative functions, implying the summations are as well.
we use multiplicity and the fact that d ∣ n ∑ λ ( d ) = { 1 0 if n is a perfect square otherwise . the first part becomes zero. and the remaining f ( p k ) = d ∣ p k ∑ ( μ ( p k ) τ ( p k ) ) = 1 − 2 + 3 − 4 + . . . + ( − 1 ) k ( k + 1 ) = ⎩ ⎪ ⎨ ⎪ ⎧ 2 k + 2 2 − k − 1 if k is even if k is odd so f ( 4 1 ) = − 1 , f ( 8 3 ) = − 1 , f ( 9 7 ) = − 1 since f is multiplicative: f ( 3 3 0 0 9 1 ) = f ( 4 1 ) f ( 8 3 ) f ( 9 7 ) = − 1 ∗ − 1 ∗ − 1 = − 1 . so the final answe is 0 + ( − 1 ) = − 1